KELALAIAN PPAT ATAS PERBUATAN MELAWAN HUKUM ANAK TIRI PEMBELI TERHADAP TUNA AKSARA - Leonard, Tommy; Benny , Benny (IBLAM LAW REVIEW, 2023)
The deed made by PPAT is an authentic official document so that PPAT in making deeds must be in accordance with the procedures of the Government Regulation of the Republic of Indonesia concerning Regulations on the Position of Land Deed Making Officers. However in making PPAT deeds, it is often found that the lack of professionalism of PPAT in carrying out legal actions results in the deeds made by PPAT experiencing losses to the parties in the future. This research was conducted so that PPAT is able and able to carry out their duties well in serving the unemployed community who want to do legal actions. This research uses normative juridical case study research with the approach of laws and regulations and government regulations. It is still found in case study number : 186/Pdt.G/2020/PN.Dpk. that PPAT was negligent in carrying out its duties in making Deed of Sale and Purchase No.168/2015 for the illiterate. therefore, PPAT does not carry out its proper obligations and is contrary to Article 22 of Government Regulation No.37 of 1998. Based on the results of the determination, the Deed of Sale and Purchase No.121./2016 is invalid and null and void.